Psychological Interventions for Young People With Psychotic Disorders: A Systematic Review - Gergov, Vera; Milic, Branka; Löffler-Stastka, Henriette; Ulberg, Randi; Vousoura, Eleni; Poulsen, Stig (Frontiers in Psychiatry, 2022)
Background: Psychotic disorders are commonly accompanied by intense psychological burden, and psychological interventions are usually needed in order to reduce the symptoms and help in maintaining or improving the level of psychological and social functioning after the onset of psychosis. The evidence-base for treating young people at risk for psychosis and adults with psychotic disorders is accumulating. Yet, pervasive systematic literature reviews that would include patients from the full age range being the most essential period for the risk of developing a psychotic disorder, a wide range of psychological interventions, and various types of clinical trials, have been lacking. The aim of this systematic review is to fill the gap by presenting the current research evidence from clinical trials on the effectiveness of psychological interventions for treating young people (12-30) with psychotic disorders. Methods: A systematic search was conducted in PubMed and PsycINFO followed by a 3-step screening process based on the PICOS strategy. Risk of bias of the included studies was assessed by the Mixed Methods Appraisal Tool. Extracted data from the included studies is reported using a narrative synthesis. Results: Of the 1449 publications screened, 40 from 25 studies were included in the review. Of these, 10 studies reported results from cognitive or behavioral therapy, nine from cognitive remediation therapy (CRT), and six from other types of therapies (i.e., integrative interventions combining psychoeducation and family/group interventions). All but one study found the target interventions to be effective, but the results mostly did not differ significantly from the control conditions in reducing symptoms and improving functioning, preventing relapses and hospitalization, or improving psychological or family variables. The most consistent findings were from CRT, showing more improvement in cognitive functioning compared to control conditions while not being superior in reducing symptom severity. Integrative interventions might be effective in treating young people suffering from psychotic disorders. Conclusion: There is some evidence that psychological interventions are effective for young people with psychotic disorders. However, with regard to symptom severity, psychotherapy does not outperform control conditions, and the results do not strongly favor any specific type of treatment.